1984
DOI: 10.1104/pp.74.4.962
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Light-Dependent Inorganic Carbon Uptake by Isolated Spinach Chloroplasts

Abstract: The light-dependent accumulation of radioactively labeled inorganic carbon in isolated spinach (Spinacia orwcea L.) chloroplasts was determined by silicone oil filtering centrifuption. Intact chloroplasts, darkincubated 60 seconds at pH 7.6 and 23°C with 0.5 millimolar sodium bicarbonate, contained 0.5 to 1.0 millimolar internal inorganic carbon.The stromal pool of inorganic carbon increased 5-to 7-fold after 2 to 3 minutes of light. The saturated internal bicarbonate concentration of illuminated spinach chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…However, some electrons originated from PSII might also be rerouted toward O 2 reduction (PSI-Mehler reaction, mitochondrial respiration, etc.). To test these possibilities, we added, prior to illumination, 2-hydroxyacetaldehyde (glycolaldehyde), an effective inhibitor of phosphoribulokinase (Sicher, 1984), or carbonyl cyanide m-chlorophenyl hydrazone (CCCP), an uncoupler of membrane potential preventing ATP synthesis in mitochondria and chloroplasts. In the presence of these inhibitors, both J H2 Table I.…”
Section: Resultsmentioning
confidence: 99%
“…However, some electrons originated from PSII might also be rerouted toward O 2 reduction (PSI-Mehler reaction, mitochondrial respiration, etc.). To test these possibilities, we added, prior to illumination, 2-hydroxyacetaldehyde (glycolaldehyde), an effective inhibitor of phosphoribulokinase (Sicher, 1984), or carbonyl cyanide m-chlorophenyl hydrazone (CCCP), an uncoupler of membrane potential preventing ATP synthesis in mitochondria and chloroplasts. In the presence of these inhibitors, both J H2 Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Plants were raised from seed in controlled environment chambers providing 700 ,umol m-2 s-', PPFD, with a 9 h photoperiod, a 23°C day/18°C night cycle and 65% relative humidity. Plants were raised in large plastic trays containing vermiculite and were watered daily with complete mineral nutrient solution (22 Enzyme measurements were usually performed at 27°C by injecting 20 to 50 uL of the chloroplast suspension directly into mL reaction mixture containing 50 mM Hepes-NaOH (pH 7.6), 1 mM MgCl2, 0.2 mm NAD+, and unit of Glc6-P dehydrogenase from Leuconostoc mesenteroides. Assays were initiated with 2 mm Glcl-P and increased absorbance was measured at 340 nm.…”
Section: Plant Materialsmentioning
confidence: 99%
“…However, when the external CO 2 concentration was increased, the concentration difference was lower than expected, suggesting a possible loss of carbon from the stroma or a decrease of stroma pH (Werdan and Heldt, 1972;Sicher, 1984). In addition, Heber and Purczeld (1978) showed that even though the permeability of the chloroplast membrane to HCO 3 2 is very low, some The traditional resistance-based approach is compared with results determined from the reaction-diffusion model.…”
Section: Leakage Of Hcomentioning
confidence: 99%